Thermogravimetric kinetic analysis of Malaysian poultry processing waste material under inert and oxidative atmospheres - Aniza, N. (Universiti Malaysia Pahang, 2016)
The aim of this work is to investigate the thermal behaviour of Malaysian poultry waste under oxidation and inert atmospheres. The poultry processing dewatered sludge (PPDS) derived from poultry waste was considered as a raw material. The study was conducted in the LABSYS Evo Setaram thermogravimetric analyser (TGA). The temperature was ramped from 30°C to 800°C in oxygen and nitrogen atmospheres at heating rates 5, 10, 15, and 20 K/min. The devolatilization process was more reactive in combustion than that in pyrolysis as evaluated from the derivative thermogravimetric (DTG) peak height and peak temperature at the second stage. In addition, a kinetic parameter called the activation energy of TGA combustion was consistently higher than pyrolysis at each conversion. The activation energy ranged from 127.32 to 245.47 kJ/mol and 88.86 to 133.13 kJ/mol for TGA under combustion and pyrolysis, respectively. The results of the TGA analysis indicate that the combustion and pyrolysis process significantly affect the degradation process of PPDS. The sample fuel properties and activation energy data obtained in this study may be beneficial for further development of thermochemical conversion (TCC) application of biomass through the computational fluid dynamics (CFDs) software. © Universiti Malaysia Pahang.